Guide to Byzantine Art - McClanan , Anne (Open textbook library., 2021)
The “Beginner’s guide” introduces foundational concepts, such as the chronology of Byzantine history, sacred imagery, and wearable objects. Subsequent sections are arranged chronologically, covering the Early Byzantine period (c. 330–700), the Iconoclastic Controversy (c. 700s–843), the Middle Byzantine period (843–1204), the Latin Empire (c. 1204–1261), and the Late Byzantine period (c. 1261–1453) and beyond. These sections include thematic essays on Byzantine art and architecture, essays that focus on key works (subtitled artworks in focus or architecture in focus), and essays that explore Byzantium’s relationships with other cultures (subtitled cross-cultural perspectives). Finally, we have included questions for study or discussion to encourage teachers, students, and other readers to engage with videos and other content on the Smarthistory website which could not be included in this book format but which we believe richly compliments what is presented here.